Menilai Kualitas Pilkada dalam Era Pandemi: Studi di Kabupaten Indragiri Hulu, Riau - Hasanuddin Hasanuddin; Auradian Marta; Wan Asrida (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
This study intends to explain and elaborate on the quality of the Pilkada in the pandemic era which was held in Indragiri Hulu Regency in 2020. The Pilkada held in 2020 was very different from the previous Pilkada because it was threatened by the spread of the COVID-19 pandemic. Therefore, it is interesting to assess the quality of the Pilkada in Indragiri Hulu Regency during this pandemic. This study uses a qualitative approach with sources of information from research informants, documents, research journals, audio-visual materials, and data from online media. The data collected is then analyzed qualitatively by using the theory of the quality of elections and democracy. The results of the study show that the 2020 Regional Head Elections in Indragiri Hulu have not been carried out freely and fairly, there are still money politics practices, violations of health protocol rules which are important policies in the Pilkada during the pandemic. However, on the other hand, there are still positive results in the implementation of the Indragiri Hulu Pilkada, namely increasing the political participation of the community in exercising their voting rights. Based on these findings, it is concluded that the quality of the Pilkada in Indragiri Hulu Regency is still low and does not meet the principles of quality and integrity elections.